Angiogenesis in potentially malignant lesions and carcinomas during experimental oral carcinogenesis: a preliminary study in the hamster cheek pouch - Aromando, Romina F.; Raimondi, Ana Rosa; Pérez, Miguel A.; Trivillin, Verónica Andrea; Schwint, Amanda Elena; Itoiz, Maria Elina (Int Inst Anticancer Research, 2014)
Fil: Aromando, Romina F.. Universidad de Buenos Aires. Facultad de Odontología; Argentina